UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK MELALUI MEDIA KINTAR PADA PEMBELAJARAN BAHASA INDONESIA KELAS II SD NEGERI TENEMBAK ALAS KABUPATEN ACEH TENGGARA - Juredah Juredah; Pangulu A Karim Nst; Nurlaili Nurlaili (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The aim of this research is to determine the reading ability of students aged 7-8 years before and after using Kincir Pintar (Smart KINTAR) media in Indonesian language learning to improve reading ability at SDN Tenembak Alas, Southeast Aceh Regency. The research used is a type of classroom action research. The subjects used were all second grade students aged 7-8 years at SDN Tenembak Alas, totaling 26 students. The results of the pre-cycle research showed that children's reading ability still experienced problems in recognizing letters, memorizing and spelling letters. Of the 26 children, 19 children were categorized as unable to read (73%) and 7 children were able to master reading skills (27%). In the first cycle, data was obtained that 26 children's reading abilities were still low, 8 children were unable to read (31%) and 18 children were able to master reading skills (69%) as expected. In cycle II research was carried out by improving the difficulties faced by children to obtain maximum improvement. In cycle II there was a significant increase, of the 26 children in the very good reading ability category there were 22 people (84%) while in the category of mastering reading skills according to expectations there were 4 there are no children (16%) and there are no children in the not yet improved category.